Model of Innovation Process in Communal Capital Companies : Case Study of MPWiK Wrocław - Olejczyk, Zdzisław (Model procesu innowacji w spółkach komunalnych : studium przypadku MPWiK Wrocław, 2010)
The article presents the conditions and characteristics of restructuring processes of Polish communal companies facing their operation to become a part of an open market, showing the transformation of this sector into a globalised economy. On the basis of the Business Model Innovation concepts, a case study of renewal in a classical Polish communal company, which is Municipal Waterworks and Sewers in Wrocław, is presented. Theoretical concept in the domain of enterprise renewal and positive results achieved in this process are collated. Applied methods together with achieved effects are also presented. These considerations may trigger further discussion about efficient ways of the realisation of this process, which is difficult but necessary in Polish communal companies.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, S. 129-143
Keywords: corporate renewal; utilities sector